2021
DOI: 10.21203/rs.3.rs-730129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural insights into the gating mechanism of human Cx43/GJA1 gap junction channel

Abstract: Connexin family proteins assemble into hexameric hemichannels in a cell membrane, which dock together between two adjacent membranes to form gap junction intercellular channels (GJIChs). The most ubiquitously expressed connexin Cx43 plays important roles in numerous biological processes. Here we report cryo-EM structures of Cx43 GJIChs at 3.1–3.6 Å resolutions, which show dynamic conformational changes of N-terminal helices (NTHs) caused by pH change or C-terminal truncation. Cx43 GJIChs in a channel-closing c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…With a functional Cx43 synthetic cell system, we turned our attention to suppressing Cx43 nanopore activity. Previous work in cells showed that Cx43 function is sensitive to cytoplasmic domain modification, 61 and recent Cryo-EM structures of connexon pores, 44,45,48 including Cx43’s, 46,47 present an opportunity to use structure-guided design to engineer inhibition of Cx43. For Cx43, two solved structures show that the N-terminus provides key contacts at the bottom of the pore (cytoplasmic side) and faces inward toward the vacant channel (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a functional Cx43 synthetic cell system, we turned our attention to suppressing Cx43 nanopore activity. Previous work in cells showed that Cx43 function is sensitive to cytoplasmic domain modification, 61 and recent Cryo-EM structures of connexon pores, 44,45,48 including Cx43’s, 46,47 present an opportunity to use structure-guided design to engineer inhibition of Cx43. For Cx43, two solved structures show that the N-terminus provides key contacts at the bottom of the pore (cytoplasmic side) and faces inward toward the vacant channel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, several pore structures of connexins have recently been solved by Cryo-EM, opening the door for structureguided design of an activatable pore. [44][45][46][47][48] Here we report the light-activated assembly of a connexon nanopore in synthetic cells and the subsequent release of internal contents. We re-engineer connexin-43 (Cx43) 46,47 with a bulky protease recognition domain, which allows membrane-protein association but prevents nanopore function in the membrane.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…At a pH of 6.9, the open state is favored: the transition between the closed and open state involves structural changes (in the secondary structure) in the first transmembrane domain, movement of the second to the fourth transmembrane domain and structural stabilization of the cytoplasmic loop [ 36 , 38 ]. The pharmacological inhibition of hemichannels formed by Cx43 have been tested in cerebral ischemia and in myocardial ischemia models, in which a large number of hemichannels are usually opened.…”
Section: Structure Of Cxs and Panxsmentioning
confidence: 99%
“…Here, we report the light-activated assembly of a connexon nanopore in synthetic cells and the subsequent release of internal contents. We re-engineer connexin-43 (Cx43) , with a bulky protease recognition domain, which allows membrane protein association but prevents nanopore function in the membrane. After enzymatic digestion, Cx43 rapidly assembles into a functional nanopore, releasing contents into the extracellular space.…”
Section: Introductionmentioning
confidence: 99%